Dual Glutathione‐S‐Transferase‐θ1 and ‐μ1 Gene Deletions Determine Imatinib Failure in Chronic Myeloid Leukemia. Issue 6 (4th September 2014) - Davies, A; Giannoudis, A; Zhang, J E; Austin, G; Wang, L; Holyoake, T L; Müller, M C; Foroni, L; Kottaridis, P D; Pirmohamed, M; Clark, R E
<x xml:space="preserve">Abstract</x> Approximately 40% of patients with chronic myeloid leukemia (CML) receiving imatinib fail treatment. There is an increased risk of CML in subjects with (i) deletions of genes encoding glutathione‐S‐transferase (GST)‐θ1 (GSTT1) and ‐μ1, (GSTM1) and (ii) the GST‐π1 (GSTP1) single‐nucleotide polymorphism (SNP) Ile105Val (GSTP1*B; rs1695); however, their effects on imatinib treatment outcome are not known. Here, we assess the role of these GSTs in relation to imatinib treatment outcome in 193 CML patients. Deletion of GSTT1 alone, or in combination with deletion of the GSTM1 gene, significantly increased the likelihood of imatinib failure (P = 0.021 and P < 0.001, respectively). The GSTP1*B SNP was not associated with time to imatinib failure. Losses of the GSTT1 and GSTM1 genes are therefore important determinants of imatinib failure in CML. Screening for GSTT1 and GSTM1 gene deletions during diagnosis may identify patients who may be better treated using an alternative therapy. Clinical Pharmacology & Therapeutics (2014); 96 6, 694–703. doi:10.1038/clpt.2014.176